IMPLEMENTASI MEDIA AUDIO VISUAL CHATGPT TERHADAP MINAT BELAJAR PADA MATA PELAJARAN SENI BUDAYA (MUSIK PIANIKA) SISWA KELAS XI DI SMA NEGERI 1 TARUTUNG TAHUN 2025/2026 - Neti Pera Berutu; Andar Gunawan Pasaribu; Testi Bazarni Zebua; Eben Haezarni Telaumbanua; Boho Parulian Pardede (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the positive and significant impact of the implementation of ChatGPT audio-visual media on learning interest in Arts and Culture (Pianica Music) among eleventh-grade students at SMA Negeri 1 Tarutung in the 2025/2026 academic year. The method used in this study was a quantitative research method. The population was all 173 eleventh-grade students of SMA Negeri 1 Tarutung in the 2025/2026 academic year, and 51 students were selected as the research sample using a random sampling technique. Data were collected using a 30-item closed-ended questionnaire. The results of the data analysis show that there is a positive and significant influence of the implementation of ChatGPT audio visual media on the learning interest in the Arts and Culture subject (Pianica Music) of class XI students at SMA Negeri 1 Tarutung in the 2025/2026 Academic Year, this is proven through the following data analysis: 1) Analysis requirements test: a) a positive relationship test obtained rxy = 0.509> rtable (a = 0.05, n = 51) = 0.279. b) A significant relationship test obtained tcount = 4.134> ttable (a = 0.05, dk = n-2 = 49) = 2.021. 2) Influence test: a) Regression equation test, obtained regression equation Y ̂=